Affective network and default mode network in depressive adolescents with disruptive behaviors - Mi Kim S; Park SY; Kim YI; Son YD; Chung U; Min KJ; Han DH (Neuropsychiatric Disease and Treatment)
Sun Mi Kim,1 Sung Yong Park,1 Young In Kim,1 Young Don Son,2 Un-Sun Chung,3,4 Kyung Joon Min,1 Doug Hyun Han1 1Department of Psychiatry, School of Medicine, Chung-Ang University, Seoul, 2Department of Biomedical Engineering, Gachon University of Medicine and Science, Incheon, 3Department of Psychiatry, School of Medicine, Kyungpook National University, 4School Mental Health Resources and Research Center, Kyungpook National University Children’s Hospital, Daegu, South Korea Aim: Disruptive behaviors are thought to affect the progress of major depressive disorder (MDD) in adolescents. In resting-state functional connectivity (RSFC) studies of MDD, the affective network (limbic network) and the default mode network (DMN) have garnered a great deal of interest. We aimed to investigate RSFC in a sample of treatment-naïve adolescents with MDD and disruptive behaviors.Methods: Twenty-two adolescents with MDD and disruptive behaviors (disrup-MDD) and 20 age- and sex-matched healthy control (HC) participants underwent resting-state functional magnetic resonance imaging (fMRI). We used a seed-based correlation approach concerning two brain circuits including the affective network and the DMN, with two seed regions including the bilateral amygdala for the limbic network and the bilateral posterior cingulate cortex (PCC) for the DMN. We also observed a correlation between RSFC and severity of depressive symptoms and disruptive behaviors.Results: The disrup-MDD participants showed lower RSFC from the amygdala to the orbitofrontal cortex and parahippocampal gyrus compared to HC participants. Depression scores in disrup-MDD participants were negatively correlated with RSFC from the amygdala to the right orbitofrontal cortex. The disrup-MDD participants had higher PCC RSFC compared to HC participants in a cluster that included the left precentral gyrus, left insula, and left parietal lobe. Disruptive behavior scores in disrup-MDD patients were positively correlated with RSFC from the PCC to the left insular cortex.Conclusion: Depressive mood might be correlated with the affective network, and disruptive behavior might be correlated with the DMN in adolescent depression. Keywords: resting-state functional connectivity, major depressive disorder, disruptive behaviors, limbic network, default mode network